Elucidating Electric Field-Induced Rate Promotion of Brønsted Acid-Catalyzed Alcohol Dehydration - Dinakar, Bhavish; Westendorff, Karl S.; Torres, Juan F.; Dakhchoune, Mostapha; Groenhout, Katelyn; Ewell, Nathan; Surendranath, Yogesh; Dincă, Mircea; Román-Leshkov, Yuriy (Journal of the American Chemical Society, 2025)
Applied potentials have been demonstrated as a powerful tool to promote heterogeneous Brønsted acid catalysis by orders of magnitude, leveraging interfacial electric fields to stabilize protonated intermediates. However, the use of flat two-dimensional electrodes with inherently low active site densities limits the application of conventional thermochemical characterization techniques that can probe the nature of catalytic active sites. Here, we use kinetic analyses with an electrostatics-based model to elucidate the intricacies of potential-induced rate promotion, employing liquid-phase dehydration of 1-methylcyclopentanol catalyzed by carboxylic acid groups on carbon nanotubes as a probe system. Using a basket electrode to directly polarize catalyst powder, we demonstrate that thermocatalytic reaction rates can be promoted by 100,000-fold, exhibiting a log–linear dependence on applied potential with rate-potential scalings as high as 125 ± 4 mV per 10-fold rate increase. In agreement with model predictions, we show that lower ionic strengths attenuate potential sensitivity, resulting from a weakening of the interfacial electric field that interacts with the acidic proton. Furthermore, we experimentally confirm the model-predicted “isokinetic potential” (at ∼0.6 V vs Ag/AgCl)the potential at which all rate scaling lines at various ionic strengths intersect, making the rate independent of ionic strength. Base titrations reveal that only ∼8% of the carboxylic acid sites are catalytically active, yet these same active sites are operational at the highest and lowest potentials. Collectively, our results provide a key methodology for modeling catalytic effects of electric fields, quantifying active sites under applied potential, and demonstrating fundamental principles of electric field-induced rate promotion.